2023
DOI: 10.3389/fcell.2023.1173794
|View full text |Cite
|
Sign up to set email alerts
|

Distinct human skeletal muscle-derived CD90 progenitor subsets for myo-fibro-adipogenic disease modeling and treatment in multiplexed conditions

Abstract: Chronic muscle injuries, such as massive rotator cuff tears, are associated with progressive muscle wasting, fibrotic scarring, and intramuscular fat accumulation. While progenitor cell subsets are usually studied in culture conditions that drive either myogenic, fibrogenic, or adipogenic differentiation, it is still unknown how combined myo-fibro-adipogenic signals, which are expected to occur in vivo, modulate progenitor differentiation. We therefore evaluated the differentiation potential of retrospectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 59 publications
(101 reference statements)
0
2
0
Order By: Relevance
“…Our findings explain in part this discrepancy by demonstrating that PDGFRβ protein is not uniformly expressed by all SC and its detection is assay dependent. Another study demonstrated the direct contribution of PDGFRβ lineage myogenic cells to muscle regeneration 14 but identification of these cells was performed using the preplating technique and long-term cultures, both are known for inducing expression of different markers than those observed in native tissues 16,17 . In order to overcome these limitations and to unequivocally prove that functional subset of PDGFRβ + SC exist in RC muscle, we combined two complementary techniques: microscopy was used to directly observe PDGFRβ + Pax7 + SC in native RC muscle tissue and FACS analysis was used for identification and sorting of fresh cells isolated from non-injured RC based on the co-expression of GFP and characteristic SC markers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings explain in part this discrepancy by demonstrating that PDGFRβ protein is not uniformly expressed by all SC and its detection is assay dependent. Another study demonstrated the direct contribution of PDGFRβ lineage myogenic cells to muscle regeneration 14 but identification of these cells was performed using the preplating technique and long-term cultures, both are known for inducing expression of different markers than those observed in native tissues 16,17 . In order to overcome these limitations and to unequivocally prove that functional subset of PDGFRβ + SC exist in RC muscle, we combined two complementary techniques: microscopy was used to directly observe PDGFRβ + Pax7 + SC in native RC muscle tissue and FACS analysis was used for identification and sorting of fresh cells isolated from non-injured RC based on the co-expression of GFP and characteristic SC markers.…”
Section: Discussionmentioning
confidence: 99%
“…1 and Supplementary Fig. S1) as well as human 12,13,17 muscle myogenic perivascular cells, a fraction of RC muscle GFP + cells (25 ± 0.8%) coexpressed CD146 (Fig. 4f,g).…”
Section: Pdgfrβ Marks a Novel Subset Of Functionally Myogenic Satelli...mentioning
confidence: 94%